EFEK KOMPOSISI BIODIESEL TERHADAP PARAMETER KUALITAS BAHAN BAKAR DAN UNJUK KERJA MESIN (PERBANDINGAN BIODIESEL SAWIT DENGAN BIODIESEL JARAK CASTOR) - Fajar, Rizqon; Suryantoro, Taufik; Sugiarto, Bambang; Setiawan, Frans (MESIN, 2006)
Biodiesel is the mono alkyl esters oflong chain fatty acids derivedfrom renewable lipid sources.Biodiesel as asubstitute ofpetroleum dieselfuel has some advantages: itproduces cleaner exhaust gas, betterin lubrication, and doesnt need engine modification. This paper presents the results ofresearch concerningthe effect ofdifferentfatty acid composition ofbiodiesel onfuel quality and its performance in diesel engine.For this purpose three different fuel sample were tested, Indonesian diesel fuel (solar) as a reference,blending solar 70%- oil palm methyl ester 30%(B-3 sawit) and blending ofsolar 70%- castor methylester 30 %(B-30 castor) . All ofthese fuels are tested using Hydra diesel engine, single cylinder indirectinjection (IDI). The test results shows that the performance (peak pressure in the cylinder) ofthreefuels arequite similar, however the two biodiesel blends show lower emission in smoke, hydrocarbon, and CO atdifferent injection timings and different loads. For NOx emission, it is slightly higher. B-30 castor containsmore unsaturatedfatty acids than B-30 sawit and therefore produced higher emission bfNOx. Beside, castormethyl ester contains an extra hydroxyl group in ricinoleic acid that probably leads to lower smoke andhydrocarbon compared to B-30 sawit. It is still aquestion that CO emission ofB-30 castor higher than ofB-30sawit. Research in the effect of chemistry andfatty acid composistionof biodiesel on the emission areneeded to be able describe mechanism ofCO, hydrocarbon andNOxformationfrom biodiesel.